Material collectors recyclable insert in Natal-Brazil (Revista LIDER, 2020)
This article presents some results of a master's research concluded in 2015 that investigated the socio- productive insertion of recyclable material collectors in Natal, Brazil. Since 2004, the municipal actions led to inclusion of waste pickers cooperatives, encouraging democratic management of these individuals. In 2010, the term of a new law governing the management of solid waste at the national level has ratified such municipal solution, establishing the formation of recycling cooperatives as a viable alternative to the social inclusion of these workers. However, several barriers are experienced by these organizations. This study aims to demonstrate the progress and difficulties encountered by pickers cooperative in Natal. This is case study, which used as the main instrument to conduct semistructured interviews with workers, in addition to observing the collector of the work at the headquarters of the two organizations surveyed.